2011
DOI: 10.1007/s00234-011-0850-6
|View full text |Cite
|
Sign up to set email alerts
|

The entire dural sinus tree is compressed in patients with idiopathic intracranial hypertension: a longitudinal, volumetric magnetic resonance imaging study

Abstract: Patients with IIH not only exhibit bilateral stenoses of the TS as has been reported, but volume changes of their entire dural sinus system also occur. The potential etiopathological and diagnostic roles of these changes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 21 publications
3
37
0
2
Order By: Relevance
“…The potential association between SSDD with PT and IIH lacks clinical evidence and needs further investigation. Several imaging features suggest the presence of IIH, including an empty sella [12][13][14], increased diameter of the optic nerve sheath (ONS) [15,16], flattened posterior sclera [15,17], vertical tortuosity of the optic nerve [15,18,14], transverse sinus stenosis [19,20], and decreased ventricle size [21]. These findings suggest that the association between SSDD with PT and IIH can be preliminarily evaluated by imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The potential association between SSDD with PT and IIH lacks clinical evidence and needs further investigation. Several imaging features suggest the presence of IIH, including an empty sella [12][13][14], increased diameter of the optic nerve sheath (ONS) [15,16], flattened posterior sclera [15,17], vertical tortuosity of the optic nerve [15,18,14], transverse sinus stenosis [19,20], and decreased ventricle size [21]. These findings suggest that the association between SSDD with PT and IIH can be preliminarily evaluated by imaging.…”
Section: Introductionmentioning
confidence: 99%
“…However, all patients had documented IIH and some degree of venous sinus abnormality (stenosis, atresia or both) that could cause outflow abnormalities and influence hemodynamics across the entire dural sinus system, as has been proposed by others. 23 …”
Section: Discussionmentioning
confidence: 99%
“…[84] In another study Rohr et al found volume changes in the entire dural sinus system in IIH patients becoming normal after treatment and they suggested that ICP changes are linked to volume decrease of the whole sinus tree. [85] Other studies have demonstrated improvement in these stenoses after CSF removal. [86,87] It has also been postulated that following a relatively minor increase of ICP, a possible abnormal flexibility of transverses sinuses in this group could lead to a significant sinus stenosis and increase venous pressure unlike in normal individuals.…”
Section: New Insights From Neuro-imaging and Bilateral Transverse Sinmentioning
confidence: 93%